ANALYSIS OF THE CONTRIBUTION OF THE PROFILE OF THE LEADER-OWNER TO THE FINANCIAL PERFORMANCE OF THE CAMEROON INDIVIDUAL ENTERPRISE - SIMO KAMGAING, Boniface; MIMCHE KOUOTOU, Anicet Clément (Revue du contrôle, de la comptabilité et de l’audit, 2020)
This study aims to verify the influence of the personal and managerial characteristics of the owner-manager on the financial performance of the individual company. We collected our data from a face-to-face questionnaire with 152 Cameroonian companies. Our analyzes show that all the companies selected are sole proprietorships from different sectors of activity. Moreover, the binary logistic regression tells us that: the manager’s level of education has no effect on the residual result, however, his training on the activity, his experience, his ability to innovate, his ability to invest exert a significant and positive influence on the residual result indirectly on the financial performance of the individual company. Similarly, when the executive is more than 40 years old, he exercises a significant and positive influence on the result of his business and thus on the financial performance of the individual company.